2021
DOI: 10.1155/2021/3985697
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Expression of Connexin43 in Cardiac Injury Induced by S-Band and X-Band Microwave Exposure in Rats

Abstract: Although the effects of microwave exposure on the heart have gradually become the focus of domestic and foreign scholars, the biological effects caused by different doses and different frequency bands of exposure are still unclear. In this study, we will investigate the damaging effect of S-band and X-band microwave composite exposure on cardiac structure and function, as well as the pathophysiological significance of Cx43 in cardiac conduction dysfunction after exposure. We used S- and X-band radiation source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The aforementioned results show that the heart function of the rats in this model was damaged, while it is known that functional changes and structural damage are frequently interrelated. Koniari et al [ 27 ] and Yin et al and Zhang et al [ 28 , 29 ] found that 7–30 days after microwave irradiation of rats at 2.5, 5, 10, and 50 mW/cm 2 , the myocardial fibers' arrangement was disordered, the structure of the intercalated discs was blurred, the mitochondria were swollen and cavitated; the increase in the radiation dose aggravated the existing lesions. In this study, the rats' myocardial structure and ultrastructure were observed under an optical microscope and transmission electron microscope, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned results show that the heart function of the rats in this model was damaged, while it is known that functional changes and structural damage are frequently interrelated. Koniari et al [ 27 ] and Yin et al and Zhang et al [ 28 , 29 ] found that 7–30 days after microwave irradiation of rats at 2.5, 5, 10, and 50 mW/cm 2 , the myocardial fibers' arrangement was disordered, the structure of the intercalated discs was blurred, the mitochondria were swollen and cavitated; the increase in the radiation dose aggravated the existing lesions. In this study, the rats' myocardial structure and ultrastructure were observed under an optical microscope and transmission electron microscope, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Our group previously established stable animal models to evaluate the nonthermal effects of microwaves ( Supplementary Figure S2 ), and the nonthermal effects on the hippocampus, heart, and testis were evaluated. Our data suggested that power-density-dependent injuries could be detected in these tissues [ 10 , 25 , 48 , 49 ]. In this study, we exposed rats to a multifrequency microwave of 1.5 GHz and 2.8 GHz, the body temperature was monitored both before and immediately after exposure, and no obvious changes were observed.…”
Section: Discussionmentioning
confidence: 97%
“…Most reports evaluated the biological effects and corresponding mechanisms using microwaves with a single frequency at the indicated average power density [ 27 , 28 , 29 ]. Our group reported that different frequency microwaves, including the S band, L band, and X band, impaired hippocampal functions, caused cardiac injury, and damaged the blood-testis barrier via multiple mechanisms [ 10 , 30 , 31 , 32 ]. However, people are always exposed to such a complex environment in daily life, which includes microwaves with varied frequencies, power densities, and so on.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single and composite exposure of S-and X-bands microwave radiation could cause the activity of myocardial enzymes increase, heart rate increase, disordered myocardial ber arrangement, mitochondrial cavitation, and intercalation disc structure uncompleted. Also, the expression and distribution of Cx43 related to cardiac electrical conduction are reduced [7]. The current studies employing cardiomyocytes as a model, however, was insu cient, and the cell models used were rat-derived H9C2 cell lines or primary rat cardiomyocytes [8].…”
Section: Introductionmentioning
confidence: 99%